A problemática da escrita musical para guitarra, na obra de Mario Castelnuovo-Tedesco: análise editorial da Sonata op. 77 (Omaggio a Boccherini) e proposta de edição e digitação da Suite op. 133 - Lopes, André Castilho (2015)
Mario Castelnuovo-Tedesco foi um dos mais produtivos e versáteis compositores do século XX. Entre óperas, oratórias, balés, música para filmes, coro, harpa, piano, órgão, violino, viola e violoncelo, deixou mais de cem obras escritas para guitarra solo, incentivado, essencialmente, pela figura de Andrés Segovia. Na presente monografia, iremos debruçar a nossa pesquisa na análise editorial da Sonata op.77 (Omaggio a Boccherini), a partir da edição de Andrés Segovia (Schott, 1935), Angelo Gilardino (Bèrben, 2007) e do próprio manuscrito. Propomos também três edições distintas da obra Suite op. 133, cujo manuscrito - disponibilizado por Lisbeth e Diana Castelnuovo-Tedesco, que permanece apenas para consulta na Library of Congress (E.U.A.) -, se nos revelou como fundamental. Com esse propósito, traremos à colação um enquadramento biográfico do compositor, das obras em análise, bem como uma análise formal das mesmas; Abstract: The issue of music written for guitar, in the work of Mario Castelnuovo Tedesco: editorial analysis of the Sonata op. 77 (Omaggio the Boccherini) and proposed Suite op. 133 edition Mario Castelnuovo-Tedesco was one of the most productive and versatile composers of the twentieth century. Among operas, oratorios, ballets, film music, choir, harp, piano, organ, violin, viola and cello, Castelnuovo left more than one hundred works written for solo guitar, encouraged mostly by Andres Segovia. In this monograph, we will focus our research on the editorial analysis of Sonata op.77 (Omaggio a Boccherini), taking as a starting point the editions of Andrés Segovia (Schott, 1935) and Angelo Gilardino (Bèrben, 2007), as well as the manuscript itself. We also propose three different editions Suite op. 133, whose manuscript - available from Lisbeth and Diana Castelnuovo-Tedesco and remaining for consultation in the Library of Congress (USA) only -, was shown to be fundamental to us. For this purpose, we will draw a biographical framework of the composer, of the works under review, as well as a formal examination of the aforementioned works.